IDENTIFICATION OF MATHEMATICAL MODEL IN THE FORM OF POLYNOMIAL RECURRENT NEURAL NETWORK AND ADJUSTMENT OF ELECTRIC DRIVE WITH SERIES-WOUND MOTOR - Orlovskiy, I. A. (Radio Electronics, Computer Science, Control, 2011)
Mathematical models of electric drive with a series-wound motor in the form of polynomial recurrent neural networks (PRNN) have been synthesized using its operational data. The methods of identification of drive parameters and drag torque dependence on motor speed were studied, setting special operating modes and different types of equations describing parameters non-linearity. A PI speed controller was adjusted according to the obtained model in the form of PRNN.